Platelet Behaviour in Normal Pregnancy, Pregnancy Complicated by Essential Hypertension and Pregnancy-Induced Hypertension - Morrison, R; Crawford, J; MacPherson, M; Heptinstall, S (Thrombosis and Haemostasis, 1985)
Platelet behaviour was studied throughout pregnancy in a group of women who remained normotensive and a group with essential hypertension (EHT). Women who developed pregnancy-induced hypertension (PIH) were also studied together with a group of non-pregnant female controls. We determined the sensitivity of platelets to arachidonic acid (AA) and determined the effects of dazoxiben, a thromboxane synthetase inhibitor, on AA-induced platelet behaviour.A marked increase in platelet reactivity was evident in all three groups throughout pregnancy; platelets became more sensitive to AA and less sensitive to the inhibitory effects of dazoxiben. The change was apparent as early as 16 weeks gestation. In normotensive pregnancy and in EHT platelet behaviour had returned to normal six weeks after delivery. Platelets from women who developed PIH were more sensitive to AA than those from the other pregnant women and platelet reactivity had not returned to normal six weeks after delivery.The results indicate that alterations in platelet behaviour may contribute to the vascular complications that are known to be associated with pregnancy and with PIH in particular.
Keywords: Pregnancy; Essential hypertension; Pregnancy-induced hypertension; Platelets; Dazoxiben; Arachidonic acid; Thromboxane A2